Effect of ultrasonic amplitude on microstructure and properties of wire arc additive manufactured ultra-high strength steel deposited metal - Tianli Zhang; Weifeng Li; Wen Wu; Lianyong Xu; Donghai Hu; Geng Chen; Wei Li; Erika Hodúlová (Journal of Materials Research and Technology)
In this paper, the AWS A5.28 E120C–K4 metal powder-cored wire with the addition of 1% CeO2 was developed to match the strength and toughness of ultra-high strength steel deposited metal. The influence mechanism of ultrasonic amplitude on the microstructure, inclusion and mechanical properties of deposited metal by wire arc additive manufacturing was investigated by optical microscopy, electron microscopy and mechanical testing. The results show that with the increase of ultrasonic amplitude from 0 μm to 50 μm and 100 μm. The segregation of TiC–CeAlO3 and Ce2O2S composite rare earth composite inclusions in the deposited metal at the grain boundary is reduced, and they are dispersed on the austenite grain boundary. The ultrasonic cavitation and cooling effects are more pronounced, more high melting point non-metallic oxides are formed, which provide nucleation sites for the solidification of subsequent welds, and the weld grains are refined. The nucleation sites of acicular ferrite are further increased, the multiphase segmentation structure is more obvious, and the impact toughness is further improved. The ultrasonic amplitude of 100 μm was applied compared with that of 0 μm, the average inclusion size of deposited metal is reduced by approximately 23.4%. The tensile strength, yield strength and impact toughness of the deposited metal increased from (793 MPa, 700 MPa, 55.8J) to (870 MPa, 796 MPa, 73.2J). Therefore, the applied ultrasonic amplitude has a positive effect on optimising the microstructure and inclusion size of the deposited metal in wire arc additive manufacturing of ultra-high strength steel, as well as improving the mechanical properties.